Caracterización y selección fenotípica de genotipos superiores de coffea canephora pierre en el banco de germoplasma de la eetpichilingue del iniap. - Plaza Avellán, Luis Fernando (2012)
This study aimed to generate scientific information field to estimate the level of variability and the existence of superior genotypes in the germplasm bank of the EET-Pichilingue INIAP. We performed a univariate analysis of descriptive statistics for the agronomic traits considered productive and health research, also conducted a principal components analysis, to know and confirm that outweigh discriminated variables. To describe the relationships between variables using a correlation analysis to identify variables associated with production. It also conducted a cluster analysis of individuals selected for presenting high performance, to identify individuals with greater similarity. The results determined the high variability in the majority of variable except with 5.66 % cherry. Meanwhile the total variable tree branches and total branches of production were identified as most associated with the performance. In addition, selected genotypes with higher attributes within accessions COFENAC-005, NP-2024, COFENAC-004 and COFENAC-003, which reached a plant height ranging from 240 to 325 cm, also had high yields with 28, 3 kg, 28.2 kg, 26.15 kg and 24 kg of coffee cherry 7, whereas, in the presence of pests was less susceptible to attack by stain iron and berry borer with 20%, in terms leaf miner sheet was more susceptible to 48%.